2017
DOI: 10.1002/ange.201701420
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte Effects on the Conformational Dynamics of a DNA Hairpin at Ambient and Extreme Environmental Conditions

Abstract: The structural dynamics of aDNA hairpin (Hp) are studied in the absence and presence of the two natural osmolytes trimethylamine-N-oxide (TMAO) and urea at ambient and extreme environmental conditions,i ncluding high pressures and high temperatures,byusing single-molecule Fçrster resonance energy transfer and fluorescence correlation spectroscopy. The effect of pressure on the conformational dynamics of the DNAHpisinvestigated on asingle-molecule level, providing novel mechanistic insights into its conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 44 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Most recent studies using FRET to monitor biomolecular conformational transitions involves single molecule (sm)FRET. To our knowledge, there are only two published studies to date of biomolecular folding based on smFRET under HP, one HP smFRET study on DNA hairpin formation [41] and the other on protein folding, both using a capillary system similar to that previously described for use in HP fluorescence correlation measurements [42]. Progress can still be made in rendering the HP capillary system more reliable and easier to use.…”
Section: On the Importance Of Observablesmentioning
confidence: 99%
“…Most recent studies using FRET to monitor biomolecular conformational transitions involves single molecule (sm)FRET. To our knowledge, there are only two published studies to date of biomolecular folding based on smFRET under HP, one HP smFRET study on DNA hairpin formation [41] and the other on protein folding, both using a capillary system similar to that previously described for use in HP fluorescence correlation measurements [42]. Progress can still be made in rendering the HP capillary system more reliable and easier to use.…”
Section: On the Importance Of Observablesmentioning
confidence: 99%
“…An unusual observation during this work is that DNA appears to also aggregate in the presence of mannitol because it is removed less than what should have been the negative control of water (see Figure 2F and 5F). The more compact shape of DNA 43 and RNA 44 was favored in high TMAO concentrations. It is also possible that the neutral mannitol could cause DNA to lose its charge, similar to the study of silica particles being neutralized in the presence of the neutral, protecting osmolyte, glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…There appeared to be flocculation of the DNA along with the virus in the mannitol system. TMAO has been shown to enhance compact conformations of DNA 43 and RNA, 44 but little is known on how mannitol affects nucleic acids. The mechanism of osmolyte flocculation of nucleic acids should be explored and may be a future method to purify plasmid and other DNA or RNA therapeutic products.…”
Section: Discussionmentioning
confidence: 99%
“…These strong urea nucleobase interactions are quantified by various experimental and theoretical approaches (Gao et al 2017;Patra et al 2017;Miner and García 2017). Guinn et al showed relatively favorable interactions of urea compared with water with different regions of nucleic acids structures, like, heterocyclic aromatic ring, methyl, carbonyl and phosphate O, amino N, and sugar (C and O) (Guinn et al 2013).…”
Section: Experimental Evidence Of Urea-aromatic Stacking Interactionsmentioning
confidence: 99%
“…Urea has long been used as an analytical tool to characterize the ubiquitous thermodynamic forces stabilizing biomolecular structures. Recent FRET studies indicated an increase in enthalpy and entropy of the RNA/DNA hairpins in the presence of high concentration of urea (Holmstrom and Nesbitt 2014;Holmstrom et al 2015;Patra et al 2017). A rugged folding free energy surface of DNA was observed which involves a number of quasi-open intermediate conformations (Sarkar et al 2009).…”
Section: Experimental Evidence Of Urea-aromatic Stacking Interactionsmentioning
confidence: 99%